ACTA2‐AS1 suppresses lung adenocarcinoma progression via sequestering miR‐378a‐3p and miR‐4428 to elevate SOX7 expression. (7th October 2020) - Ying, Kangtai; Wang, Ling; Long, Guangyan; Lian, Chan; Chen, Zhe; Lin, Wei
Abstract: Lung adenocarcinoma (LUAD) is the most common histological subtype of lung cancer. The abnormal expression of long noncoding RNAs (lncRNAs) can facilitate or suppress the development of malignant tumors. lncRNA actin alpha 2, smooth muscle antisense RNA 1 (ACTA2‐AS1) has been reported to function as a tumor suppressor in liver cancer, nevertheless, its influences on LUAD remain to be investigated. In this paper, ACTA2‐AS1 was identified as a downregulated lncRNA in LUAD samples and cells. Functionally, ACTA2‐AS1 overexpression restrained cell proliferation but accelerated cell apoptosis in LUAD. In addition, we determined the suppressive effect of ACTA2‐AS1 on LUAD cell invasion, migration, and epithelial–mesenchymal transition progress. Mechanistically, ACTA2‐AS1 exert functions as a competing endogenous RNA through serving as a sponge for microRNA‐378a‐3p (miR‐378a‐3p) and microRNA‐4428 (miR‐4428) to elevate SRY‐related high‐mobility group box 7 (SOX7) expression. Importantly, SOX7 silencing could recover the ACTA2‐AS1‐mediated cell functions. To summarize, ACTA2‐AS1 suppresses the malignant processes of LUAD cells through sequestering miR‐378a‐3p and miR‐4428 to augment SOX7 expression.